Studying Human-computer Interaction for Social Good: The Case of Digital Government Evaluation and Re-design Project - Avouris, Nikolaos; Sintoris, Christos; Katsini, Christina (Proceedings of the 22Nd Pan-Hellenic Conference on Informatics, 2018)
Inclusion of social good in computer science education has been proposed as an approach that demonstrates computing's social relevance and potential for positive societal impact, thus providing students with a motivating vision over the subject. This is particularly important in the context of human-computer interaction courses that can relate to real life situations more easily than other theoretical or more technical subjects. This paper presents a teaching intervention in the context of a master's level course of Human-Computer Interaction and Design of Interactive Systems, during which a group of students were asked to address a critical problem, i.e. to evaluate and re-design typical Greek e-government sites. Given the importance of efficient and effective public sector services for the society's cohesion and citizens' inclusion, and the demand for improving their usability, in particular for the Greek case, it is argued here that this approach of teaching human-computer interaction, situates the theory and methods of the course in a socially relevant context, motivating the students and increasing the learning effect of the teaching intervention.
Keywords: design and evaluation of interactive systems; e-government services evaluation; teaching human-computer interaction